Digital strategies for sustainable production in the timber construction sector: informative models for resource optimisation - Cognoli, Roberto; Calvano, Michele (Techne (Florence, Italy : 2011), 2025)
This paper describes the technology transfer process involving expertise developed by the University of Camerino and Sapienza University of Rome in the field of timber digitalisation and parametric informative models. The research was applied in collaboration with an Interior Contract company in the Lazio region for the design of a complex wooden architectural element. The adoption of a methodology based on informed digital models, spanning from design to fabrication, enabled a reduction in production waste (-30%) and an optimisation of design and production time (-20%). The case study demonstrates how the synergy between multidisciplinary research expertise and the industrial sector can generate efficient and replicable solutions. From an academic perspective, the experimentation has strengthened the collaboration between universities and industry, fostering the development of transferable know-how for future applications.